2017
DOI: 10.1016/j.paid.2016.10.042
|View full text |Cite
|
Sign up to set email alerts
|

The conditional indirect effects of suicide attempt history and psychiatric symptoms on the association between intimate partner violence and suicide ideation

Abstract: Background Women seeking shelter from intimate partner violence (IPV) experience heightened risk for suicide ideation and attempts compared to abused and non-abused women in the general population. However, few theory-guided studies have examined what cognitive-emotional symptoms might underlie this increased risk. Methods Guided by fluid vulnerability theory, this cross-sectional, survey study tested whether depressive symptoms, PTSD symptoms, and hopelessness mediate the association between IPV (coercive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…Prior research on help-seeking samples of primarily women has supported coercive control as the main form of IPV associated with suicidal ideation (Frye et al, 2006; Leone, 2011; Wolford-Clevenger & Smith, 2017). However, the current study only partially supports this pattern in dating couples, finding that some dimensions of emotional abuse were associated with suicidal ideation, while physical assault was not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research on help-seeking samples of primarily women has supported coercive control as the main form of IPV associated with suicidal ideation (Frye et al, 2006; Leone, 2011; Wolford-Clevenger & Smith, 2017). However, the current study only partially supports this pattern in dating couples, finding that some dimensions of emotional abuse were associated with suicidal ideation, while physical assault was not.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that individuals in relationships characterized by coercive control experience greater suicidal ideation than those in relationships troubled by physical assault resulting from situational conflict (Frye, Manganello, Campbell, Walton-Moss, & Wilt, 2006; Johnson, 1995; Leone, 2011). Theoretically, being coercively controlled by one’s partner may elicit greater emotional pain and hopelessness—both which are risk factors for suicide ideation (Baumeister, 1990; Wolford-Clevenger & Smith, 2017). …”
mentioning
confidence: 99%
“…In general, violence has many negative consequences for women and for minors exposed to abuse (Evans, Davies, & Dilillo, ; Fusco & Fantuzzo, ), and it diminishes the quality of life of the women concerned, who are victims in terms of suffering health problems, such as depression, anxiety, and suicidal thoughts/attempts (Lucena et al, ; Wolford‐Clevenger & Smith, ). The stress for the victim caused by violence can lead to suicidal behavior, based on cognitive responses related to sadness, anxiety, and despair (Rudd, ).…”
Section: Introductionmentioning
confidence: 99%
“…The stress for the victim caused by violence can lead to suicidal behavior, based on cognitive responses related to sadness, anxiety, and despair (Rudd, ). The percentage of suicide attempts among women suffering from violence is, therefore, higher than among women who have never experienced violence (Haarr, ; McLaughlin, O'Carroll, & O'Connor, ; Wolford‐Clevenger & Smith, ). For example, research by Rhodes, Lauderdale, He, Howes and Levinson () shows that women victims of violence in the US were five times more likely to attempt suicide than those who had not been abused.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation